The Development of a Survey Instrument to Assess Aboriginal and Torres Strait Islander Students’ Resilience and Risk for Self-Harm - McCalman, Janya; Bainbridge, Roxanne Gwendalyn; Redman-MacLaren, Michelle; Russo, Sandra; Rutherford, Katrina; Tsey, Komla; Ungar, Michael; Wenitong, Mark; Hunter, Ernest (Frontiers in Education, 2017)
Background Australian policies for Aboriginal and Torres Strait Islander well-being outline the importance of local community-based interventions; for adolescents, school-based programs have been identified as beneficial. However, there is a lack of localized data to determine levels of resilience and risk and thus whether programs are effective. This paper describes the challenges and opportunities in collaboratively designing and piloting a localized survey instrument to measure Indigenous students’ resilience and upstream risk factors for self-harm and the resultant instrument. Methods A participatory action research approach was used to engage education staff, health-care providers, students, and researchers to design and pilot the survey instrument. A six-phased process facilitated survey development: (1) defining the logic and exploring the evidence; (2) understanding and tailoring for context; (3) testing for feasibility and relevance; (4) testing for appropriateness and comprehension; (5) facilitating survey administration; and (6) refining the instrument. Processes in each phase were recorded and transcribed with thematic analysis used to identify key challenges and opportunities arising during development. Results Four key challenges and opportunities were identified: (1) the relevance of international survey instruments for Indigenous Australian students; (2) accounting for distinct environments; (3) the balance between assessing risk and protective factors; and (4) tailoring for literacy levels and school engagement. The final Student Survey instrument comprised 4 demographic and 56 resilience, risk, service use, and satisfaction questions. The T4S will be administered routinely on annual student intake. Discussion and conclusion The six-phased participatory processes resulted in a tailored instrument that could identify the critical resilience and upstream risk factors facing a cohort of Indigenous students who attend boarding schools for secondary education. Challenges were resolved collaboratively and the pilot results were directly translated to education practice and its integration with health services. Our results suggest that both the phased process of developing the T4S and the instrument itself can be adapted for other Indigenous adolescent well-being and/or self-harm prevention programs.